Clinical Care Coordination in Medically Complex Pediatric Cases: Results From the National Survey of Children With Special Health Care Needs. (May 2019) - Hofacer, Rylon D.; Panatopoulos, Andrew; Vineyard, Jared; Tivis, Rick; Nguyen, Elaine; Jingjing, Niu; Lindsay, Ryan P.
This study uses a secondary analysis of the 2009-2010 National Survey of Children with Special Health Care Needs (NS-CSHCN) to describe care coordination (CC) for children with medical complexity (CMC). Chi-square test, t test, and multivariate logistic regression statistical tests are used to determine the relationships and differences between sources of CC and factors associated with receiving clinic-based CC for CMC and their family. Among CMC, 66.47% received no CC support and 25.73% received clinic-based CC. In multivariate models, families reporting dissatisfaction with communication between health care providers or reporting family-centered care were less likely to receive clinic-based CC. Families were more likely to receive clinic-based CC if they had younger children, lower household income, and greater school absenteeism. Clinic-based CC is associated with improved communication between health providers but must become more family-centered and minimize student absenteeism for the CMC population.